Bromatologic composition of sugar cane bagasse added to hen caged manure according to storage period - Oliveira, Mauro Dal Secco de; Malheiros, Euclides Braga (Pesquisa Agropecuaria Brasileira, 1991)
A trial was carried out to study the bromatologic composition of sugar cane bagasse (SCB) added to hen caged manure (HCM) and stored for 0; 20; 40 and 60 days, (treatments A, B, C and D respectively) in a completely randomized design with nine replications. The effect of storage gradually increased crude protein and gross energy of SCB and HCM mixture up to 60 days. Minimal stocking of 20 days is recomended.
Keywords: roughage; concentrate; crude protein; gross energy